The perspective on scientific research of the department of geography since their inception - Vovk Korže, a (Journal for Geography, 2013)
Fifty years of geography in Maribor is an opportunity to look at the scientific research activities since the beginning of 1962 until today. Bibliographies of geographers from Maribor include various activities, which included geography. Addition to the traditional division of geography on the physical, social, educational and regional geography, we have a growing number of active geographers in the field of environmental geography. The article presents a brief look at the activity area and changes in the orientation that are monitored especially since Slovenia joined the EU.
Keywords: geography; research work; Department of Geography Maribor; Faculty of Arts Maribor